Integration now : Alexander v. Holmes and the end of Jim Crow education - Hustwit, William P. (The University of North Carolina Press, 2019)
"Recovering the history of a landmark Supreme Court case that has received surprisingly little attention from scholars, William P. Hustwit assesses the significant role that Alexander v. Holmes (1969) played in integrating the South's public schools and argues that the Alexander decision was ultimately more decisive than Brown v. Board in terminating public school segregation. Although the Brown ruling has rightly received the lion's share of attention, its ambiguous implementation language -- 'all deliberate speed' -- led to more than a decade of delays and resistance by whites. Alexander v. Holmes required 'integration now, ' and less than a year later, thousands of children were attending integrated schools"--